Something important for special education in Malaysia - Musa, Shahrul Hapizah; Md Zain, Elia; Ismail, Muhd Zulkifli; Mat Hussin, Hifzan; Nordin, Mohd Norazmi (Karadeniz Technical University, 2021)
Special education has always been special in the framework of the Malaysian education system. Discussions on special education are incomplete if not instilled with love and concern for students with special needs (MBK). Special education makes all parties involved always sensitive to the needs of MBK. In the face of various changes and current needs, special education must always be relevant and consistent in providing the best for all involved. Special education needs to be strengthened as much as possible so that consistency in service can be maintained. To ensure the sustainability of the best services to MBK which consists of various categories such as vision problems, hearing problems and learning problems, several things need to be improved in line with the current situation. This brief descriptive study was conducted to obtain general views from special education teachers on aspects that need to be given attention by the ministry of education Malaysia to make special education always at the forefront. The survey was conducted online to special education teachers around the district of Batu Pahat, Johor, Malaysia for that purpose and the data obtained were analyzed descriptively using SPSS. The findings of this study indicate 11 important aspects that need to be improved for special education. It is hoped that the results of this study are given due attention by the authorities to make the management of special education always the best.